An experimental and CFD study on gas flow field distribution in the growth process of multi‐walled carbon nanotube arrays by thermal chemical vapor deposition. Issue 12 (11th November 2016) - Li, Mingjie; Xu, Zhaopeng; Li, Zhaobin; Chen, Yan; Guo, Jingwei; Huo, Huimei; Zhou, Hangyu; Huangfu, Huichao; Cao, Zehui; Wang, Haiyan
Abstract : Multi‐walled carbon nanotube arrays grown on the central position are more aligned and longer than those on the bottom. A computational fluid dynamics model was employed to investigate the gas flow field impact on the Multi‐walled carbon nanotube arrays growth. The results show that gas circulations appear after carrier gas and carbon source are injected into the quartz tube. Abstract : Multi‐walled carbon nanotube arrays (MWCNTAs) were grown by thermal chemical vapor deposition (TCVD) in a horizontal furnace reactor. The scanning electron microscopy (SEM) results show that MWCNTAs grown on the bottom and the central of the quartz tube are different in one experiment. Moreover, the MWCNTAs grown on the central position are more aligned and longer than those on the bottom. A computational fluid dynamics (CFD) model was employed to investigate the gas flow field impact on the MWCNTAs growth. The results show that gas circulations appear after carrier gas and carbon source are injected into the quartz tube. Because of the existence of gas circulations, the gas flow field at the central of the quartz tube is more stable, which is conducive to the growth of MWCNTAs. The CFD simulation results match well with the experimental data.